Can self-compassion and mindfulness predict psychological wellbeing in individuals with endometriosis? Findings from an online survey - Federica Facchin; Francesca Grosso; Emanuela Saita; Paolo Vercellini; Francesco Pagnini (BMC Women's Health)
Abstract Background Endometriosis presents diagnostic challenges and has profound impacts, encompassing physical and psychological symptoms, relationship difficulties, and disruptions in daily life. The emotional burden is pervasive, intensified by feelings of anxiety, depression, guilt, and shame. Despite extensive exploration of risk factors such as pelvic pain, knowledge about protective factors for mental health in this population is limited. Thus, this study aims to investigate whether self-compassion and mindfulness are associated with enhanced psychological wellbeing in individuals with endometriosis. Methods This cross-sectional study involved 653 participants aged 18 years or older, self-reporting a clinical or surgical diagnosis of endometriosis. Data collection occurred online via Qualtrics from May 11 to August 24, 2022. Sociodemographic and endometriosis-related data were collected using a researcher-made questionnaire. Psychological wellbeing, self-compassion, and mindfulness were assessed using validated self-report questionnaires. Results Out of 1,153 survey accesses, 653 participants (75%) provided complete responses and were included. Self-compassion and mindfulness exhibited a positive correlation with psychological wellbeing. In a hierarchical multiple regression model, controlling for confounding factors, both variables significantly increased the explained variance (ΔR 2  = 0.315). However, only the association between psychological wellbeing and self-compassion remained statistically significant. Conclusions Self-compassion emerges as an important protective factor for psychological wellbeing in the context of endometriosis. These findings, coupled with recent studies, emphasize the significance of promoting self-compassion in the psychological treatment of individuals with endometriosis, especially among the young and recently diagnosed.